Supportive Communication Between Caretakers and Membersof TheYogyakarta Hamur Community in Overcoming Chronic Trauma in Broken-Home Adolescents - Suciati Yahono; Shenia Benesti (USIM Press, 2024)
AL-I’LAM –J. Contemp. Islam. Comm. & Media Vol. 3, Issue 1 Page(81-99)